Use of precipitated sulphur in pretrolatum for the topical treatment of knemidocoptic mange (Knemidocoptes sp) in two roosters - Cazorla Perfetti, Dalmiro (2016)
The short communication shows the results of a clinical trial to evaluate the topical application of precipitated sulphur in petrolatum (10%) in the treatment of chronic feet skin lesions of knemidocoptic mange in two roosters in Coro city, Falcon state, Venezuela. The diagnosis was made by clinical and laboratory examination of scrapings of cutaneous lesions processed with KOH 10% and microscopically observed. The topical treatment was performed every 3 days for 1 month. The evaluation of the treatment was done by observing the evolution of the lesions and scraping of the knemidocoptic lesions and the assessment of the side-effects was done by clinical observation. Both birds recovered from the injuries without side effects. The mixture of precipitated sulfur in petrolatum appears as a simple and inexpensive alternative for the topical treatment of knemidocoptic mange in Gallus gallus domesticus.